Role and contribution of pulmonary CD103+ dendritic cells in the adaptive immune response to Mycobacterium tuberculosis. (January 2017) - Koh, Vanessa Hui Qi; Ng, See Liang; Ang, Michelle Lay Teng; Lin, Wenwei; Ruedl, Christiane; Alonso, Sylvie
Abstract: Despite international control programmes, the global burden of tuberculosis remains enormous. Efforts to discover novel drugs have largely focused on targeting the bacterium directly. Alternatively, manipulating the host immune response may represent a valuable approach to enhance immunological clearance of the bacilli, but necessitates a deeper understanding of the immune mechanisms associated with protection against Mycobacterium tuberculosis infection. Here, we examined the various dendritic cells (DC) subsets present in the lung and draining lymph nodes (LN) from mice intra-tracheally infected with M. tuberculosis . We showed that although limited in number, pulmonary CD103 + DCs appeared to be involved in the initial transport of mycobacteria to the draining mediastinal LN and subsequent activation of T cells. Using CLEC9A-DTR transgenic mice enabling the inducible depletion of CD103 + DCs, we established that this DC subset contributes to the control of mycobacterial burden and plays a role in the early activation of T cells, in particular CD8 + T cells. Our findings thus support a previously unidentified role for pulmonary CD103 + DCs in the rapid mobilization of mycobacteria from the lungs to the draining LN soon after exposure to M. tuberculosis, which is a critical step for the development of the host adaptive immune response.